SISTEM INFORMASI PENDAFTARAN PESERTA DARUL ARQAM DASAR BERBASIS WEBSITE PADA IKATAN MAHASISWA MUHAMMADIYAH UNIVERSITAS MUHAMMADIYAH BULUKUMBA - Arjuna Edi; Husni Sulaiman; Awal Nur (Institut Teknologi dan Bisnis Bina Adinata, 2023)
Information systems in organizations today continue to grow, if in the past the information system was still manual with recording hardcopy files, now it is starting to be computerized so that the registration process is easier to register online through the website, the Darul Arqam Basic Registration System (DAD) of the Muhammadiyah Student Association has not utilized the use of information technology making it difficult for students of the Bulukumba Muhammadiyah University in registering students to come to the registration place to take and return the form to the registration committee Solution to find out this requires a new breakthrough, namely the use of information technology by building a website-based online registration system. The research method used is System Development Life Cycle (SDLC) with a 5-stage waterfall model, namely requirements analysis, system design, implementation, integration and testing, operation and maintenance and design using UML, namely, use case diagrams, activity diagrams and sequence diagrams and programming applications using Xampp and sublime text and the programming language used is php and mysqli Based on functional blackbox testing can run as expected and produce a website-based online registration process.